2019
DOI: 10.1111/tra.12638
|View full text |Cite
|
Sign up to set email alerts
|

Melanin processing by keratinocytes: A non‐microbial type of host‐pathogen interaction?

Abstract: The mechanisms that regulate skin pigmentation have been the subject of intense research in recent decades. In contrast with melanin biogenesis and transport within melanocytes, little is known about how melanin is transferred and processed within keratinocytes. Several models have been proposed for how melanin is transferred, with strong evidence supporting coupled exo/endocytosis. Recently, two reports suggest that upon internalization, melanin is stored within keratinocytes in an arrested compartment, allow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…Low molecular weight components such as dimeric compounds were appreciably internalized after 1 h incubation. These data provide further confirmation to biological studies indicating that keratinocytes are able to internalize melanins as the result of a cross-talk with melanocytes, mediated by the protease-activated receptor 2 (PAR-2) and the Ras-related protein Rab11 [59,60]. Overall, our findings demonstrate that MeDHICA-melanin is able to enter the cells and activate the antioxidant system to protect skin cells from UVA-induced damage, encouraging its use as an effective component in dermo-cosmetic formulations for the treatment of skin damage, photoaging and skin cancers.…”
Section: Discussionsupporting
confidence: 79%
“…Low molecular weight components such as dimeric compounds were appreciably internalized after 1 h incubation. These data provide further confirmation to biological studies indicating that keratinocytes are able to internalize melanins as the result of a cross-talk with melanocytes, mediated by the protease-activated receptor 2 (PAR-2) and the Ras-related protein Rab11 [59,60]. Overall, our findings demonstrate that MeDHICA-melanin is able to enter the cells and activate the antioxidant system to protect skin cells from UVA-induced damage, encouraging its use as an effective component in dermo-cosmetic formulations for the treatment of skin damage, photoaging and skin cancers.…”
Section: Discussionsupporting
confidence: 79%
“…Hence, the first task where this approach can find application is the investigation of melanin fate and its redistribution in the epidermis upon stress conditions such as UV exposure 2,68 , oxidative and mechanical stress 11 , etc. Although this task is seemingly simple, the fact is that a number of questions about the melanin fate (such as the presence of "melanin dust" in the stratum corneum 13,14 ), kinetics and mechanisms of its transfer in normal and stress conditions and the degradation pathways 7,[11][12][13][14] require additional studies, in which the suggested method could be useful.…”
Section: Discussionmentioning
confidence: 99%
“…However, in later works, autophagy was demonstrated not to have a substantial effect on skin pigmentation 9 , and melanosomes were shown to be non-degradative 10 . Other mechanisms like inherent asymmetric localization of melanosomes between dividing keratinocytes could be potentially involved in a complex inhomogeneous distribution of melanin in the epidermis [11][12][13] . Hence, precise assessment of melanin distribution in different epidermal layers is required to study fundamental processes and identify melanin-related abnormalities in norm and pathology.…”
mentioning
confidence: 99%
“…Skin melanocytes and RPE cells are two mammalian cell types in which melanosomes move from the cell body to the cell periphery. In melanocytes, melanosome biogenesis is active (Raposo and Marks, 2007) and the melanosomes do not return to the cell body; they are delivered to keratinocytes from the melanocyte dendrites (Hume et al, 2001;Wasmeier et al, 2008;Fukuda, 2013;Wu and Hammer, 2014;Moreiras et al, 2019). By contrast, melanosome biogenesis is very low in the postnatal RPE (Lopes et al, 2007b).…”
Section: Discussionmentioning
confidence: 99%
“…In mammalian skin, melanosome biogenesis occurs in melanocytes (Raposo and Marks, 2007). The melanosomes then pass from the dendrites of the melanocytes to neighboring keratinocytes (Hume et al, 2001;Wasmeier et al, 2008;Fukuda, 2013;Wu and Hammer, 2014;Moreiras et al, 2019). Preceding the intercellular transfer, melanosomes must be transported and retained in the melanocyte dendrites.…”
Section: Introductionmentioning
confidence: 99%